Genetic Characterization of Serotypes A and Asia‐1 Foot‐and‐mouth Disease Viruses in Balochistan, Pakistan, in 2011. Issue 5 (2nd August 2016) - Ullah, A.; Jamal, S. M.; Romey, A.; Gorna, K.; Kakar, M. A.; Abbas, F.; Ahmad, J.; Zientara, S.; Bakkali Kassimi, L.
Summary: This study reports characterization of foot‐and‐mouth disease virus (FMDV) in samples collected from Balochistan, Pakistan. FMDV was detected by pan‐FMDV real‐time RT‐PCR in 31 samples (epithelial and oral swabs) collected in 2011 from clinical suspect cases. Of these, 29 samples were serotyped by serotype‐specific real‐time RT‐PCR assays and were confirmed by sequencing the VP1 coding region. Sixteen samples were found positive for serotype A and eight for serotype Asia‐1, whereas five samples were found positive for both serotypes A and Asia‐1. Two serotype A positive samples were found positive for two different strains of serotype A FMDV each. Phylogenetic analyses of serotype A FMDVs showed circulation of at least three different sublineages within the A‐Iran05 lineage. These included two earlier reported sublineages, A‐Iran05 HER −10 and A‐Iran05 FAR −11, and a new sublineage, designated here as A‐Iran05 BAL −11 . This shows that viruses belonging to the A‐Iran05 lineage are continuously evolving in the region. Viruses belonging to the A‐Iran05 FAR −11 sublineage showed close identity with the viruses circulating in 2009 in Pakistan and Afghanistan. However, viruses belonging to the A‐Iran05 HER −10 detected in Balochistan, Pakistan, showed close identity with the viruses circulating in Kyrgyzstan, Iran and Kazakhstan in 2011 and 2012, showing that viruses responsible for outbreak in these countries have a common origin. Serotype Asia‐1 FMDVs reported in this study all belonged to the earlier reported Group‐VII (Sindh‐08), which is currently a dominant strain in the West Eurasian region. Detection of two different serotypes of FMDV or/and two different strains of the same serotype in one animal/sample shows complexity in occurrence of FMD in the region.